VOLUME DAN KLASIFIKASI LIMBAH PENEBANGAN PADA BEBERAPA PENGUSAHAAN HUTAN DI ACEH DAN KALIMANTAN TIMUR - Sampe Radja Simarmata; Dulsalam Dulsalam (Pusat Penelitian dan Pengembangan Hasil Hutan, 1985)
A study on volume and classification of logging waste has been carried out in several forest companies in Aceh, North Sumatra, and East Kalimantan. Average wood waste volume at the logged over areas having diameter range from 10 to 39 cm with one meter in length or more were measured using the Brereton method.The results of this investigation reveal that:I. Logging waste volume in Aceh range from 26,46 to 29,08 m3/ha with an average of 27,85 m3/ha. In North Sumatra the value ranges from 22,94 to 38,66 m3/ha with an average of 28,90 m3/ha. It was formed that in East Kalimantan the logging waste ranges from22,00 to 81,94 m3/ha with an average of 52,38 m3/ha.2. The average wood waste at felling site was higher in the forest companies in East Kalimantan.3. Logging waste consists predominantly of those classified as 10 to 39 cm in diameter with 4 m length or more.4. The average volume of logging waste classifiedas 10 to 19 cm in diameter with 4 m length of more in Aceh, North Sumatra and East Kalimantan are consecutively 17,5 m3/ha,16,9 m3/ha and 24,9 m3/ha.